The effect of acorn scarification on the growth and root system size of Quercus robur L. seedlings grown in nursery containers - Mariusz Kormanek; Paweł Tylek; Jacek Banach; Zdzisław Kaliniewicz (Journal of Forest Science)
The mechanical scarification of acorns, although requiring a significant investment of resources, is a process commonly used in container nurseries for seed preparation. Its aim is to increase the number of germinating seeds and to shorten and equalise the length of their germination period. Research results indicate that scarification also affects the production of seedlings with improved biometric parameters. However, there is limited information available on improving the structure of the root system, primarily due to the limited availability of image analysis systems for these plant parts. This study employed modern measurement methods using WinRhizo and WinFolia software (Regent Instruments Inc.; Version Pro, 2022) to comparatively analyse root system parameters, focusing mainly on their structure. The parameters of pedunculate oak (Quercus robur L.) seedlings grown in polystyrene containers were compared with and without mechanical scarification, achieved by manually cutting off part of the acorn. After the end of the growing season, the parameters of all analysed seedlings (200 pieces) were determined, and a detailed analysis of the root system was performed on selected average individuals (64 pieces). Scarification resulted in an increase in the number of germinated seeds and grown seedlings, as well as an increase in the height and diameter of the root collar and a reduction in the variation of the obtained seedlings' parameters. Seedlings grown from scarified seeds were also characterised by a greater number of leaves with larger unit mass, which had smaller dimensions. The root system of seedlings grown from scarified seeds exhibited a higher average diameter and total volume of roots, as well as greater total length, surface area, and volume of fine roots, i.e. in the diameter range: 0.5 < D ≤ 2.0 mm. The obtained results confirmed the positive effect of seed scarification on germination and emergence efficiency, as well as on biometric features and the quality of the grown seedlings.